Effective management of cardiothoracic surgical wounds: a scoping review - Monedero, Alba Mínguez; Molina, Paula Posadas; Klyčmuradov, Murad; Kielė, Viktorija (Slauga. Mokslas ir praktika, 2022)
Cardiac surgery is included among the seven surgical procedures with the highest surgical site infection rate. Surgical wounds have been a major topic worldwide, having the healthcare team to face a big challenge on their management, giving a multidisciplinary approach to the patient. The following scoping review aims to capture the most effective management of the cardiothoracic surgical wound, comparing conventional and more advanced techniques. Methods. A scoping review completed of seven full text free of charge publications corresponding to the research topic. Selection criteria for publi cations were determined by researchers. A scoping review and analysis of the scientific literature was performed. Results. There is no consensus between which of the two therapies is the best for cardiac wound management. While some of the authors consider negative pressure wound therapy a better choice due to healing time, cost-effectivity and the number of complications, yet others claim that there are no differences. Despite of whether this therapy is considered a superior or equal method to wound dressings, each particular case must be individually evaluated and all methods are taken for consideration. Conclusions. Two principal methods were found for wound management - conventional wound dressings and negative pressure wound therapy. By reviewing the publications hardly any differences were found in the use of one or the other therapy.